2017
DOI: 10.1097/mpa.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

S100P in Duodenal Fluid Is a Useful Diagnostic Marker for Pancreatic Ductal Adenocarcinoma

Abstract: Analysis of S100P concentration in DF, in combination with routine screening upper GIE, may facilitate the detection of PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…Thus, measuring the expression level of S100P in pancreatic juice might help distinguish pancreatitis from tumor disease for early screening and diagnosis of PC (85). Since S100P is a specific and sensitive marker, it is possible to detect the concentration of S100P in duodenal fluid (DF) based on upper gastrointestinal endoscopy (GIE) or endoscopic ultrasonography, which may be helpful for early PDAC screening (88). In addition, evaluation of S100P expression can be combined with EUS-FNA quantitative analysis to improve the accuracy of diagnosis of PC and nontumor lesions (89)(90)(91) or be applied in fine-needle aspiration biopsy (FNAB) specimens prepared in cell blocks and smears to test for PDAC (92,93).…”
Section: S100p: An Indicator Of Early Pc Occurrencementioning
confidence: 99%
“…Thus, measuring the expression level of S100P in pancreatic juice might help distinguish pancreatitis from tumor disease for early screening and diagnosis of PC (85). Since S100P is a specific and sensitive marker, it is possible to detect the concentration of S100P in duodenal fluid (DF) based on upper gastrointestinal endoscopy (GIE) or endoscopic ultrasonography, which may be helpful for early PDAC screening (88). In addition, evaluation of S100P expression can be combined with EUS-FNA quantitative analysis to improve the accuracy of diagnosis of PC and nontumor lesions (89)(90)(91) or be applied in fine-needle aspiration biopsy (FNAB) specimens prepared in cell blocks and smears to test for PDAC (92,93).…”
Section: S100p: An Indicator Of Early Pc Occurrencementioning
confidence: 99%
“…We showed that S100P was one of the three proteins detected with high expression based on IHC in HPA (6 of 9 samples). S100P was studied to discriminated normal and PDAC samples using a higher concentration in duodenal fluid in patients with PDAC compared with the control group, presenting an AUC of 0.71 for detecting PDAC [73]. Our results showed an AUC of 0.92 for S100P using mRNA expression (Additional file 4: Figure S2).…”
Section: Discussionmentioning
confidence: 77%
“…Cystatin 6 (CST6) is overexpressed in pancreatic ductal adenocarcinoma (PDAC) cells and can stimulate PDAC cell growth by reducing the activity of intracellular cathepsin B ( Hosokawa et al, 2008 ). There is evidence that S100 calcium-binding protein P (S100P) can be used as a biomarker in duodenal fluid and fine needle aspiration biopsies for detection of PDAC, and this protein has a diagnostic sensitivity of 84.8% in biopsy samples ( Matsunaga et al, 2017 ; Aksoy-Altinboga et al, 2018 ). S100P secretes matrix metalloproteinase 9 (MMP9) and regulates the invasion of PC cells into the lymphatic endothelial monolayer, thereby promoting tumor cell invasion and metastasis ( Dakhel et al, 2014 ; Nakayama et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%